The changing C/N of aggressive aniline: Metagenomic analysis of pollutant removal, metabolic pathways and functional genes. (December 2022) - Zhang, Yunjie; Zhang, Qian; Peng, Haojin; Zhang, Wenli; Li, Meng; Feng, Jiapeng; He, Jing; Su, Junhao
Abstract: In order to optimize the degradation of high-concentration aniline wastewater, the operation of sequencing batch bioaugmentation reactors with different aniline concentrations (200 mg/L, 600 mg/L, 1000 mg/L) was studied. The results showed that the removal rates of aniline and COD in the three reactors could reach 100%. When the aniline increased to 600 mg/L, the nitrogen removal efficiency reached the peak (51.85%). The increase of aniline inhibited the nitrification, while denitrification was enhanced due to the increase of C/N ratio. But this change was reversed by the toxicity of high concentrations of aniline. The metagenomic analysis showed that when the aniline concentration was 600 mg/L, the abundance distribution of microbial samples was more uniform. The improved of aniline concentration had led to the increase of aromatic compounds degradation metabolic pathways. In addition, the abundance of aniline degradation and nitrogen metabolism genes ( dmpB, xylE, norB ) was also promoted. Graphical abstract: Image 1 Highlights: The increase of aniline concentration inhibited the nitrification of the system. The toxicity of aniline reversed the enhanced effect of C/N on denitrification. The increase of aniline within a certain range was beneficial to the secretion of EPS. The system's stability depends on the cooperation and competition of microorganisms.